Marketing Mix Factors (7Ps) Affect Decision on Enrolling into The Culinary Program of Undergraduate Students in Bangkok and Vicinity Area - Sajjatanawat, Achira; Yonwikai , Wilasinee (Dusit Thani College Journal, 2020)
The purposes of this research were to: 1) study the demographic factors, Marketing mix factors (7Ps), Psychological factors, and Decision on enrolling into the Culinary program of undergraduate student in Bangkok and vicinity area. 2) study the relationship between demographic factors and decision on enrolling into the culinary program. 3) study the Marketing mix factors (7Ps) affecting decision on enrolling into the culinary program. 4) study the Psychological factors affecting the decision on enrolling into the culinary program. The samples for the research were 400 undergraduate students who were studying on the first year in the Culinary program in Bangkok and vicinity area. The research tools were questionnaires. The data were analyzed by using descriptive statistics, frequency, percentage, mean, and standard deviation. The hypothesis was analyzed by using independent t-test, one-way ANOVA, and Multiple Regression Analysis. The hypothesis tested results show that first year undergraduate students who were studying in a culinary program with the differentiation in Gender, Domicile, Qualifications degree, Parents occupation, Household monthly income, and working experience in cooking, have no difference in decision on enrolling for the culinary program of undergraduate student in Bangkok and vicinity area. While the students who have different reason for enrolling in culinary program, will have a difference decision on enrolling into the culinary program. For the marketing mix factors (7Ps), there were 6 factors that affected the decision on enrolling into the culinary program of undergraduate student, which are Product, Price, Place, Physical evidence, and Process. While Promotion doesn’t affect the enrollment decision. And the most important factor among the marketing mix factors is Product factor. In addition, all of the Psychological factors affected the decision on enrolling into the culinary program of undergraduate student in Bangkok and suburban area. The educational institutions and related parties can use the finding of this study to improve their marketing planning and the marketing mix of higher education institutions offering culinary courses.